Dampak Positif Program Makan Bergizi Gratis (MBG) bagi Siswa : Studi Literatur - Dyah Ayu Nur Aini; Rio Ramadhan Setiawan; Jick Prasetyo Wicaksono; Gaitsa Zahira Shafira; Nazwa Isfalana Idris (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
As a strategic public policy, the Free Nutritious Meal program serves as a long-term social investment aimed at enhancing the quality of human resources. This study is directed to examine and map the positive contributions of the MBG initiative to the pillars of health, discipline levels, and academic achievement of students through a literature review method. The article search, utilizing keywords such as